Miłosz w dialogu z literackim centrum świata - Bill, Stanley S. (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
In 1986 Bernard Pivot, a French journalist and literary critic, conducted an interview with Miłosz in the television feature called Apostrophes. The conversation was an archetypal example of an encounter between a representative of the “literary centre” and an envoy from what Pascale Casanova later called “une petite littérature”. The present article discusses Miłosz’s contradictory relations with France as a centre of “world’s republic of letters”, against the background of his difficult dialogue with Pivot, and the wider context of Casanova’s theory of inequalities in the literary world. On the one hand, Miłosz felt wiser than French litterateurs, and frequently pointed out to their political naiveness and ignorance of history and the cruel reality of the world. On the other hand, however, Miłosz’s sense of superiority over Western culture was always dialectically linked to the other side of the coin: the rage of a provincial poet at the headquarters of the cultural and economical power.